IMPLICATIONS OF SOCIAL STRUCTURE AND FAMILY FUNCTION IN EARLY MARRIAGE: A STRUCTURAL FUNCTIONALISM PERSPECTIVE IN TANJUNG HARAPAN VILLAGE, TANJUNG RAYA, MESUJI - Andrian Farozi; Luthfi Salim; Faisal Adnan Reza (Jurnal Analisa Sosiologi, 2025)
This study examines how social structures influence and legitimize early marriage practices, and how these practices impact family functions in Tanjung Harapan Village, Tanjung Raya Subdistrict, Mesuji Regency. Using a descriptive qualitative approach and Talcott Parsons' structural functionalism theory, this research involved ten purposively selected informants, including underage married couples, their parents, village officials, and religious leaders. Data were collected through in-depth interviews and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that early marriage is driven by economic vulnerability, cultural normalization, peer influence, and the weak role of formal institutions, resulting in informal legitimacy that overrides state law. These conditions lead to family dysfunction, marked by financial dependence, emotional immaturity, and constrained social roles. Through the AGIL framework, this study identifies the failure of adaptation, goal attainment, integration, and latency functions within the local social system. It concludes that early marriage is not merely a personal or moral issue, but a systemic problem rooted in structural inequality. The study recommends strengthening preventive efforts through community-based education and the involvement of local institutions in promoting healthy family development.